Opposing effects of bisphosphonates and advanced glycation end-products on osteoblastic cells - Gangoiti, María Virginia (2008)
Patients with long-standing Diabetes mellitus can develop osteopenia and osteoporosis. We have previously shown that advanced glycation endproducts reduce the bone-forming activity of osteoblasts. Bisphosphonates are used for the treatment of various bone disorders, since they reduce osteoclastic function and survival, and stimulate osteoblastic bone-forming capacity. In this work we have investigated whether bisphosphonates are able to revert advanced glycation endproducts-induced deleterious effects in osteoblasts. MC3T3E1 and UMR106 osteoblastic cells were incubated with control or advanced glycation endproducts-modified bovine serum albumin, in the presence or absence of different doses of the bisphosphonates Alendronate, Pamidronate or Zoledronate. After 24–72 h of culture, we evaluated their effects on cell proliferation and apoptosis, type-1 collagen production, alkaline and neutral phosphatase activity, and intracellular reactive oxygen species production. Advanced glycation endproducts significantly decreased osteoblast proliferation, alkaline phosphatase activity and type 1 collagen production, while increasing osteoblastic apoptosis and reactive oxygen species production. These effects were completely reverted by low doses (10−8 M) of bisphosphonates. High doses of bisphosphonates (10−4–10−5 M) were toxic for osteoblasts. Nifedipine (L-type calcium channel blocker) did not affect the advanced glycation endproducts-induced decrease in osteoblastic proliferation, although it blocked the reversion of this effect by 10−8 M Alendronate. Both advanced glycation endproducts and Alendronate inhibited the activity of intracellular neutral phosphatases. In conclusion, we show that bisphosphonates revert the deleterious actions of advanced glycation endproducts on osteoblastic cells, and that these effects of bisphosphonates depend on: (a) Ca2+ influx through L-type voltage-sensitive channels, and (b) blockage of advanced glycation endproducts-induced reactive oxygen species generation.